The alarmin tandem: unraveling the complex effect of S100A8/A9 – from atherosclerosis to cardiac arrhythmias - Cozac, Dan-Alexandru; Halațiu, Vasile-Bogdan; Scridon, Alina (Frontiers in Immunology, 2025)
IntroductionInflammation plays a crucial role in the pathophysiology of cardiovascular diseases (CVDs), particularly in heart failure (HF), cardiac arrhythmias, and atherosclerotic cardiovascular disease (ASCVD). The calcium-binding proteins S100A8 and S100A9, primarily functioning as a heterodimer (S100A8/A9), have emerged as essential mediators in cardiovascular pathophysiology through the toll-like receptor 4 (TLR-4) and receptor for advanced glycation end-products (RAGE) signaling pathway. This review aims to comprehensively explore the role of S100A8/A9 in ASCVD, HF, and cardiac arrhythmogenesis, and to discuss its pathophysiological implications, clinical significance, and potential utility as a novel therapeutic target.Main textIn ASCVD, S100A8/A9 promotes endothelial dysfunction and facilitates monocyte recruitment and foam cell formation. The heterodimer amplifies vascular inflammation via TLR4 and RAGE signaling cascades, culminating in nuclear factor-kappa B activation and upregulation of proinflammatory cytokines that contribute to plaque instability. In HF patients, elevated S100A8/A9 levels correlate with disease severity and adverse outcomes through mechanisms involving cardiomyocyte death and pathological cardiac remodeling. Emerging evidence also implicates S100A8/A9 in cardiac arrhythmogenesis through electrical remodeling and pro-fibrotic effects. Despite significant advances in understanding the role of S100A8/A9 in cardiovascular pathology, significant knowledge deficiency remains. Further research is needed to elucidate cardiac-specific effects, temporal expression, and potential therapeutic applications.ConclusionS100A8/A9 plays a critical dual role in cardiovascular inflammation and repair, emerging not only as a biomarker but also as a promising therapeutic target in ASCVD, HF, and cardiac arrhythmogenesis, with potential applications for anti-inflammatory intervention. However, further research is needed to elucidate the precise mechanisms linking S100A8/A9 and CVDs and to validate therapeutic interventions targeting this pathway.